The body in the piazza : a Faith Fairchild mystery - Page, Katherine Hall (Page, Katherine Hall. Faith Fairchild mystery., 2013)
While celebrating their anniversary in Italy, amateur sleuth/caterer Faith Fairchild and her husband, the Reverend Tom Fairchild, find murder on the itinerary when a new acquaintance is killed in the Eternal City and someone tries to sabotage her former assistant's new cooking school in Florence.